In-situ activation of biomimetic single-site bioorthogonal nanozyme for tumor-specific combination therapy - Ma, Mengmeng (2024)
Copper-catalyzed click chemistry offers creative strategies for activation of therapeutics without disrupting biological processes. Despite tremendous efforts, current copper catalysts face fundamental challenges in achieving high efficiency, atom economy, and tissue-specific selectivity. Herein, we develop a facile "mix-and-match synthetic strategy" to fabricate a biomimetic single-site copper-bipyridine-based cerium metal-organic framework (Cu/Ce-MOF@M) for efficient and tumor cell-specific bioorthogonal catalysis. This elegant methodology achieves isolated single-Cu-site within the MOF architecture, resulting in exceptionally high catalytic performance. Cu/Ce-MOF@M favors a 32.1-fold higher catalytic activity than the widely used MOF-supported copper nanoparticles at single-particle level, as first evidenced by single-molecule fluorescence microscopy. Furthermore, with cancer cell-membrane camouflage, Cu/Ce-MOF@M demonstrates preferential tropism for its parent cells. Simultaneously, the single-site CuII species within Cu/Ce-MOF@M are reduced by upregulated glutathione in cancerous cells to CuI for catalyzing the click reaction, enabling homotypic cancer cell-activated in situ drug synthesis. Additionally, Cu/Ce-MOF@M exhibits oxidase and peroxidase mimicking activities, further enhancing catalytic cancer therapy. This study guides the reasonable design of highly active heterogeneous transition-metal catalysts for targeted bioorthogonal reactions.